Secure signature verification system by using Matlab / Hairol Azmi Abdullah - Abdullah, Hairol Azmi (2002)
With the widely spread usage of the computer terminal, automatic teller and data banks, there has been a corresponding increase in computer crime and growing need to protect sensitive information. Based on this observation, a system that utilizes a person's signature verification using MATLAB and some of Neural Network for identification has been proposed. This paper highlights a secure signature verification system using MATLAB and Neural Network toolbox. The main purpose is to develop a signature identification and verification system. A signature is captured in bit-map and fed into the back propagation Neural Network as input in order to train the network. After training the Neural Network is ready to perform the identification and recognition operation (matching process). A Neural Network programming has been successfully developed to verifying the signature.